Long run productivity and profitability in the British bus industry. (January 2023) - Cowie, Jonathan
Abstract: The passing of the Transport Act 1985 deregulated and privatised the bus industry in Great Britain outside of London, however failed to address the prime specified aim of reversing the long run decline in patronage. Review of the literature suggests one of the main reasons for this was due to subsequent industry consolidation that resulted in anti-competitive market structures and outcomes, i.e. inefficient production and fare levels that resulted in monopoly profits. In the current study, the British bus industry is analysed over the period 1994 to 2016 through the estimation of long run Malmquist productivity indices and supplementary profit data in order to look for evidence of such inefficient market outcomes. From the mid-point of the period reviewed however, the results for London are entirely consistent with the opposite, i.e. efficient market outcomes. This is also found to be the case for the deregulated areas, but the most striking characteristic in these areas are consistent and continual technical change declines. This is clear evidence of long-term structural decline. The policy implications are that any policy measures should be part of a package of wider policy actions that seek to improve the underlying economics of bus service provision in Great Britain. From an albeit limited amount of past research, this would appear to lie in the direction of proactive public transport initiatives and car use limiting measures.